The American Political Dictionary / Third Edition - Greenberg Milton; Plano Jack C (The Dryden Press, 1972)
Preface, Political Ideas, The United States Constitution, The Federal Union, Immigration and Citizenship, Civil Liberties and Civil Rights, Parties and Politics and Pressure Groups and Elections, The Legislative Process, The Executive, Public Administration, The Judicial Process, Finance and Taxation, Government and Business, Government and Labor, Agriculture and Environment and Natural Resources, Health and Education and Welfare, Foreign Policy and International Affairs, National Defense, State and Local Government, Index.